2012
DOI: 10.1051/0004-6361/200912994
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation in the massive star-forming region IRAS 19410+2336

Abstract: Context. The core mass functions (CMFs) of low-mass star-forming regions are found to resemble the shape of the initial mass function (IMF). A similar result is observed for the dust clumps in high-mass star-forming regions, although on spatial scales of clusters that do not resolve the substructure that is found in these massive clumps. The region IRAS 19410+2336 is one exception, having been observed on spatial scales on the order of ∼2500 AU, which are sufficient to resolve the clump substructure into indiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 76 publications
6
27
0
Order By: Relevance
“…Fig. 1 well (see also Beuther et al 2002c;Beuther & Schilke 2004;Rodón et al 2012). The interferometric observation filters out large scale structure, but the comparison to older interferometric observation at 2.6 mm by Beuther et al (2003) shows very good agreement.…”
Section: Observational Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Fig. 1 well (see also Beuther et al 2002c;Beuther & Schilke 2004;Rodón et al 2012). The interferometric observation filters out large scale structure, but the comparison to older interferometric observation at 2.6 mm by Beuther et al (2003) shows very good agreement.…”
Section: Observational Resultssupporting
confidence: 53%
“…In the calculations, we assume that the excitation temperature is equal to the kinetic temperature, which should be approximately correct at the given high densities. As temperature, 40 K is used (Rodón et al 2012) and τ is the optical depth. For the assumption of optically thin lines holds τ 1, and the factor τ/(1 − e −τ ) approaches unity.…”
Section: Appendix A: Sio Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…3 we inferred core masses of M MM1 = 545 Figure 6 shows a radius-versus-mass diagram for a significant (but not complete) sample of massive protostellar cores Rathborne et al 2007Rathborne et al , 2008Beuther et al 2002Beuther et al , 2003Beuther et al , 2005Beuther et al , 2012Molinari et al 1998;Rodón et al 2012), while the empty circles correspond to the same set of sources for which we recalculated the mass using the same dust opacity law as in this paper. The MM1 and MM2 sources are indicated as red filled circles.…”
Section: Sdc335: An Ob Cluster Progenitormentioning
confidence: 99%
“…Peter et al (2012) find companion separations between 400 and several thousand AU, stressing the necessity of high spatial resolution, Furthermore, Sana et al (2012) infer that multiple system interactions dominate the evolution of massive stars. Interferometer studies have revealed that most high-mass starforming regions fragment into multiple objects, suggesting that massive monolithic cores larger than several 1000 AU are rare, however, the degree of fragmentation varies (e.g., Cesaroni et al 2005;Beuther et al 2007bBeuther et al , 2012Zhang et al 2009;Bontemps et al 2010;Wang et al 2011;Rodón et al 2012;Palau et al 2013;Sánchez-Monge et al 2014;Johnston et al 2015). Even regions that remain single continuum sources down to arcsec resolution, mostly fragment on even smaller scales.…”
Section: Introductionmentioning
confidence: 99%